Penatalaksanaan Fisioterapi Pada Kondisi Post Fraktur Olecranon Sinistra Dengan Pemasangan Plate And Screw Di RST Dr Soedjono Magelang - Hadipurwa, Dwi Angga, Dwi Rosella Komalasari S.Fis, M.Fis (2015)
Background: Fracture the olecranon sinistra is a condition in which bone is lost ulnar proximal left that due to the pressure, overload, extreme movement so that the bone is not able to withstand. Aim of Research: To know the management of physiotherapy in reducing pain, increasing range of motion, maintaining muscle strength in patients post fractures the olecranon sinistra with mounting plate and screw by using modalities Infra red and Therapeutic Exercise. Results: After terapy for about six times the obtained result reduction in the degree of pain, in motion pain T1: 3.3 to T6: 0. increase loop segment 5 cm above T1: 23 cm to T6: 24 cm, 5 cm down T1: 26 cm to T6: 27 cm, 10 cm and above T1: 23 cm to T6: 24 cm, 10 cm down T1: 24 cm to T6: 25 cm. increase muscle strength in flexion T1: 4 to T6: 4, extensions T1: 4 to T6: 4. Increased range of motion S: T1: 2,50-300-800 to T6: 30-200-900. Conclusion: Infra Red can reduce pain in the case of post fracture the olecranon sinistra with mounting plate and screw. Exercise Therapy can increase the range of motion and increase muscle strength in the case of post fracture the olecranon sinistra with mounting plate and screw.